Low-energy extraction of lignocellulose nanofibers from fresh Musa basjoo pseudo-stem - Mayasari, Erna; Fukugaichi, Satoru; Johan, Erni; Matsue, Naoto (Communications in Science and Technology, 2023)
This study presents a novel approach for the extraction of cellulose nanofibers (CNF) and lignocellulose nanofibers (LCNF) from Musa basjoo pseudo-stems, a relative of bananas, without the need for extensive drying. Instead, wet pseudo-stems were compressed and treated with NaOH solutions at varying temperatures and durations. The extracted material exhibited the characteristic peaks of cellulose I in X-ray diffraction (XRD) patterns, similar to those obtained from dried pseudo-stems. Fourier-transform infrared (FT-IR) spectroscopy confirmed the presence of cellulose I in the treated material and lignocellulose nanofiber clearly shown at 1600-1500, 1421, 1365, and 1161 cm-1. Composition analysis by Van Soest fiber analysis revealed a higher cellulose content in the treated material of wet pseudo-stems compared to that obtained from dried pseudo-stems, indicating the effectiveness of this low-energy extraction method. Meanwhile, field-emission scanning electron microscopy (FE-SEM) images demonstrated clear LCNF in the nanometer scale fibers after NaOH treatment. Overall, this study successfully demonstrated the extraction of LCNF from wet pseudo-stems of Musa basjoo with NaOH treatment at 70°C for 3 hours with 80% extraction result, providing a more efficient and low-energy approach for utilizing waste from Musa basjoo and bananas.